"Grissgott" meets "Kung Fu": Multilingualism, Humor, and Trauma in Saša Stanišić's Wie der Soldat das Grammofon repariert (2006). Issue 3 (3rd July 2019) - Uca, Didem
Abstract: Bosnian-German writer Saša Stanišić's debut novel, Wie der Soldat das Grammofon repariert (2006), is a transnational Bildungsroman that portrays a young male protagonist's coming of age amidst the start of the Bosnian War and his family's decision to seek refuge in Germany. Yet, despite the protagonist's challenging circumstances, the author depicts tragedy through a comedic lens. Drawing on recent theories of narratology, multilingualism, migrant literature, trauma, humor, and popular culture, this article performs close readings of select passages to explore how Stanišić's multilingual practice utilizes humor in order to narrate the protagonist's development and his process of working through trauma.